1968
DOI: 10.1099/00221287-51-2-185
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Tube Method of Measuring Growth Rate in Neurospora crassa

Abstract: S U M M A R YThe relationship between various parameters of growth of Neurospora crassa on solid media in tubes is described. These are (a) the relationship between culture weight and linear growth rate on various media; (b) the relationship between 'lag' in growth and inoculum size on various media. This latter relationship appears to obey a log law, enabling an inoculum doublingtime to be calculated. Adaptation of the arginine auxotroph arg-I (46004) to diminution of arginine in the medium first occurred by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1969
1969
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…of the initial glucose concentration when this is the growth limiting nutrient. Gillie (1968) found that the rate of extension of Neurospora crassa colonies was proportional to the log. of the arginine concentration over the lower range, and it would thus seem that this is a general relationship for any growth limiting nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…of the initial glucose concentration when this is the growth limiting nutrient. Gillie (1968) found that the rate of extension of Neurospora crassa colonies was proportional to the log. of the arginine concentration over the lower range, and it would thus seem that this is a general relationship for any growth limiting nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of linear extension of a mycelial front of wild-type Neurospora can be as great as 0.6 cm/h (105). Although there are many conditions, such as nonoptimal temperature and genetic constitution, that will markedly diminish this rate (38,57), the rate of advance of a mycelial front on a solid medium usually depends surprisingly little on nutrition. It is the density of branching behind the front that varies dramatically (56,57).…”
Section: Miscellaneous Underexploitedmentioning
confidence: 99%
“…Although there are many conditions, such as nonoptimal temperature and genetic constitution, that will markedly diminish this rate (38,57), the rate of advance of a mycelial front on a solid medium usually depends surprisingly little on nutrition. It is the density of branching behind the front that varies dramatically (56,57). Hence, on a rich, mediocre, or poor medium, Neurospora can generally push forward a mycelial front at a rate of 10 to 14 cm/ day.…”
Section: Miscellaneous Underexploitedmentioning
confidence: 99%
“…This was made possible by an apparently sparse growth. Gillie (1968) weighed sections of mycelium of Neurospora crassa after extraction of agar and freeze-drying. Pittendrigh et al (1960) used a densitometer for optically scanning density striations in N .…”
Section: E D E L S T E I N a N D Others Discussionmentioning
confidence: 99%
“…The method chosen after some experimentation was a modification of Gillie's (1968) direct weighing procedure. Our modifications included (a) growing the colonies on cellophane-covered media, hence eliminating the need for agar extraction, (b) removing mycelia from the growth surface with sticky tape, enabling a more accurate dissection of fixed areas, and (c) repeating measurements for different growth times, hence obtaining a time sequence of the colony growth.…”
Section: E D E L S T E I N a N D Others Discussionmentioning
confidence: 99%